2021
DOI: 10.21608/ejsgs.2021.196288
|View full text |Cite
|
Sign up to set email alerts
|

Associations between age at puberty, growth traits, plasma IGF-I and leptin concentrations with reproductive performance of Rahmani and Barki male Lambs

Abstract: The present study aimed to investigate the effect of breed type and puberty status on growth performance, blood IGF-I, leptin concentrations, and the subsequent reproductive performance of Rahmani and Barki male lambs. After weaning at week 14th, two equal groups of Rahmani and Barki male lambs (n = 20 each) were used in the present study till 40 week of age. All lambs followed to tracking the growth traits and puberty development. Blood samples were collected from each lamb every two weeks for IGF-I, leptin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The overall means for MM, LS, AS, Host, pH, colour, Visco, VOL, NC, LR, LU, DR and DU were 69.93%, 94.40%, 6.76%, 20.14%, 6.94, 3.30, 3.04, 0.75 mL, 53.52%, 44%, 15.78%, 19.36% and 20.86%, respectively. These means were within the range reported by the previous studies for Egyptian sheep breeds (Mahmoud, 2013;Shamiah et al, 2015;Abdel-Khalek et al, 2018;Abdel-Mageed and Dessouki, 2018;Mansour, 2021). Shamiah et al (2015) stated that means of VOL, MM, LS, AS, LR, LU, DR and DU were 0.79 mL, 81.88%, 90%, 2%, 30.38%, 45.90%, 6.56% and 17.13% in Rahmani rams, respectively and were 0.86 mL, 84.06%, 93.60%, 2%, 28.50%, 47.13%, 6.30% and 18.10% in Ossimi rams, respectively.…”
Section: Actual Means and Variation Of Semen Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…The overall means for MM, LS, AS, Host, pH, colour, Visco, VOL, NC, LR, LU, DR and DU were 69.93%, 94.40%, 6.76%, 20.14%, 6.94, 3.30, 3.04, 0.75 mL, 53.52%, 44%, 15.78%, 19.36% and 20.86%, respectively. These means were within the range reported by the previous studies for Egyptian sheep breeds (Mahmoud, 2013;Shamiah et al, 2015;Abdel-Khalek et al, 2018;Abdel-Mageed and Dessouki, 2018;Mansour, 2021). Shamiah et al (2015) stated that means of VOL, MM, LS, AS, LR, LU, DR and DU were 0.79 mL, 81.88%, 90%, 2%, 30.38%, 45.90%, 6.56% and 17.13% in Rahmani rams, respectively and were 0.86 mL, 84.06%, 93.60%, 2%, 28.50%, 47.13%, 6.30% and 18.10% in Ossimi rams, respectively.…”
Section: Actual Means and Variation Of Semen Traitssupporting
confidence: 90%
“…Comparing Ossimi and Assaf sheep breeds raised in Egypt, Abdel-Mageed and Dessouki, (2018) reported that means of VOL, LS and AS were 1.50 mL, 70.90% and 9.80%, in Ossimi rams, respectively and were 1.75 mL, 89.87% and 6.97%, in Assaf rams, respectively. Comparing Barki and Rahmani breeds, Mansour (2021) revealed that means of VOL, MM, LS, AS in Barki rams were 0.68 mL, 68.36%, 81.55% and 15.83%, respectively, the same author added that Barki breed was higher than Rahmani breed in all the studied semen characteristics. The present results were superior than those of Abdel-Khalek et al ( 2018) who stated that actual means of VOL, MM, LS and AS were 0.21 mL, 45.5%, 41.9% and 18.1% in Ossimi rams, respectively.…”
Section: Actual Means and Variation Of Semen Traitsmentioning
confidence: 87%
“…An elastic tape was used to measure the circumference of the scrotum at the point of maximum circumference of the paired testes. Previously described methods were used to assess testes volume ( El-Zelaky et al ., 2011 ; Mansour, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides being capable of adapting to harsh desert conditions, they also produce substantial amounts of meat, wool, and milk under those conditions ( El-Wakil et al ., 2008 ; Abousoliman et al ., 2020 ). The Barki sheep is also a source of income for Egyptian farmers and a source of meat for the locals ( Mansour, 2021 ). Therefore, there is a great deal of interest in understanding how these animals grow and what traits they possess to improve the quality of the meat they produce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation